Desigualdades sociais e ação coletiva: propostas teóricas para o estudo das práticas associativas em contexto local - Nunes, N. (CIES e-Working Papers, 2012)
This proposal is a theoretical and analytical discussion that wants to deepen the study of collective action from the perspective of social inequalities. Proposals that seek to explore prospects for research in local contexts, examining the relevance and impact of social inequality on collective actors and associative practices of agents and respective dynamics of cultural identities generated. Anchoring in the sociology of social classes, it is enriched with other recent contributions, for the parameterization of a holistic program for the study of collective action in modernity.